Evolution of diagnosis standards for diabetes in China and blood glucose management for special populations - ZOU Huimin, WANG Suijun (Zhenduanxue lilun yu shijian)
The prevalence of diabetes in China has been increasing annually. In 2021, the prevalence rate of diabetes reached 13.79% among individuals aged 20–79, with an undiagnosed rate as high as 56.0%. This indicates that China's diabetes prevention and control faces significant challenges. Diabetes is a chronic metabolic disease. Poor blood glucose control increases the risk of serious complications such as cardiovascular disease, kidney disease, retinopathy, and neuropathy, which impose a heavy burden on both individual health and socioeconomic development. Early detection of diabetes and the implementation of effective interventions are crucial for preventing complications. Currently, China's diabetes diagnosis primarily adopts international standards, using the 75g oral glucose tolerance test (OGTT) and glycated hemoglobin (HbA1c) as the gold standards for diagnosis. However, due to disparities in detection technologies and other factors, these methods still have certain limitations in clinical practice, especially in primary medical institutions where diabetes screening capacity and standardization level require further improvement. In addition, China demonstrates relatively low levels of awareness, treatment, and control rates of diabetes. According to 2021 data, the awareness rate of diabetes in China was 36.5%, the treatment rate was 33.2%, and the control rate was 49.2%. Although China has made some progress in diabetes prevention and treatment in recent years, there is still significant room for improvement. To address the challenges of diabetes prevention and treatment, a series of diabetes guidelines and consensus statements have been released by domestic experts, emphasizing the individualized and stratified management of diabetes patients. Different blood glucose control targets and treatment plans have been formulated for children and adolescents, pregnant women, and elderly patients. Meanwhile, the promotion of glucose monitoring technologies is considered an important approach to improve the rate of achieving blood glucose control targets. However, clinical attention remains inadequate for type 2 diabetes in children and adolescents, gestational diabetes, and elderly diabetes with sarcopenia, lacking standardized treatment strategies and high-quality medical evidence. For the current state of diabetes diagnosis and treatment in China, it remains imperative to further improve the diagnostic testing level, the coverage of examinations, and the ability of stratified management for different population groups.